Identification and Detection of Shigella Species from Wildlife Using Multiplex Polymerase Chain Reaction (mPCR) - Wong, Ngah Kiat (Universiti Malaysia Sarawak, UNIMAS, 2010)
Shigella spp. is Gram-negative bacteria that causes shigellosis in both developing and developed countries. Shigella spp. was reported to be the third common bacterial agent responsible for childhood diarrhoea in Malaysia. Most of the previous research on Shigella were focused on human. Hence, this study aimed to detect the occurrence of Shigella spp. from wildlife (rats, squirrels, birds, and bats) using biochemical tests and multiplex PCR assay. Biochemical tests were used to pre-identify the occurrence of Shigella spp. isolated from wildlife. Then, mPCR assay was used for simultaneous detection of virulence genes (setl A, setl B, ial and ipaH) in Shigella spp. Four isolates from a total of fifty swab samples (8%) collected from the wildlife were confirmed to be Shigella spp. using mPCR assay. The invasion plasmid antigen H (ipaH) gene was detected in all of the four isolates with two isolates from squirrels, one isolates from bat and one isolate from wild bird. On the other hand, invasion-associated locus (ial) gene was only detected in isolate from the squirrel. Both ial and ipaH genes are responsible for directing epithelial cell penetration by Shigella. This study therefore has successfully detected the occurrence of Shigella spp. from wildlife and eventually shows that animals (e.g. birds, rodents) can be vectors for Shigella spp. and have the potential to cause zoonotic infection.